Comprehensive review of shipboard maintenance management strategies - Min-Ho Park; Won-Ju Lee (Results in Engineering)
Maintenance optimization is essential in reducing a ship’s operating costs and ensuring its safety. This review aims to introduce existing literature related to shipboard maintenance management strategies and products developed in the maritime industry, and provide an overall understanding of the same by discussing both the relevant technologies and applications. Accordingly, the following maintenance strategies are extensively discussed: 1) corrective; 2) predetermined (inspection-, usage-, and time-based); 3) proactive (risk-based and reliability-centered); 4) predictive (condition-based and prognostics and health management); and 5) prescriptive. The basic concepts, application examples, and related studies for each strategy are introduced, and appropriate figures are inserted to help readers understand. Next, system diagrams, components, expected effects, and use cases for seven maintenance management products in the maritime industry are explained. Finally, literature references and products are summarized chronologically, and a discussion based on shipboard experience and future works is presented. From this review, potential readers can gain insights into the history, status, and future directions in shipboard maintenance management.